Determinants Factors of Stunting in Together in East Kambingan Village and Talang Village, Saronggi District, Sumenep Regency - Tri Agus Panatariono; Yenny Puspitasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Stunting is a chronic nutritional problem caused by inadequate nutritional intake for a long time. Stunting occurs from the womb and is only seen when the child is two years old. Stunting that is not handled quickly and appropriately is at risk of triggering health problems and not achieving optimal growth and development in children. The research design used was observational with a retrospective study approach. The sample in this study was 219 respondents who were taken from the population using simple random sampling technique. The independent variable in this study was maternal factors, while the dependent variable in this study was the incidence of stunting in children under five. To determine the relationship between research variables, the Spearman Rho correlation test was used, while the multiple logistic regression test was used to see the magnitude of the maternal risk factor for the incidence of stunting in children under five. From the results of the regression test, it is known that maternal height affects the incidence of stunting in toddlers (p-value: 0.005), mother's education affects the incidence of stunting in toddlers (p-value: 0.011) and the first age when pregnant women affect the incidence of stunting in toddlers (p value: 0.015). From the results of the study it can be concluded that the occurrence of stunting in toddlers in the East Kambingan Village and Talang Village, Saronggi District, Sumenep Regency is influenced by the mother's height, mother's education, and the mother's first age during pregnancy.